2020
DOI: 10.3390/ma13163481
|View full text |Cite
|
Sign up to set email alerts
|

Silane Treatment as an Effective Way of Improving the Reinforcing Activity of Carbon Nanofibers in Nitrile Rubber Composites

Abstract: Two different silane treatment methods were used to improve the reinforcing activity of carbon nanofibers (CNF) in acrylonitrile-butadiene rubber (NBR) composites. The first method was chemical silanization with [3-(2-aminoethylamino)propyl]trimethoxysilane (APTS) in ethanol solution, preceded by oxidation of the CNF with H2SO4/HNO3. The second method was direct incorporation of silanes during preparation of the composites (in-situ silanization). Three different silane coupling agents were used: [3-(2-aminoeth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 54 publications
0
8
0
Order By: Relevance
“…Silanes are widely known additives, used for improving the interfacial adhesion and compatibility between fillers and elastomers [ 34 ]. However, the studies mainly concern the common fillers, i.e., silica [ 35 ], carbon black and carbon nanofibers [ 36 ]. Several authors have also reported the attempts to improve the compatibility between natural fibers and elastomer by using the compatibilizer or biofiller surface modification [ 34 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Silanes are widely known additives, used for improving the interfacial adhesion and compatibility between fillers and elastomers [ 34 ]. However, the studies mainly concern the common fillers, i.e., silica [ 35 ], carbon black and carbon nanofibers [ 36 ]. Several authors have also reported the attempts to improve the compatibility between natural fibers and elastomer by using the compatibilizer or biofiller surface modification [ 34 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…On their basis, the values of the difference between the compression work and the work during deformation reduction (∆W i ) and the compression work (W ibel ) were calculated. The values of the relative attenuation coefficient were calculated based on the following Equation (4) [ 41 ]: …”
Section: Methodsmentioning
confidence: 99%
“…It is generally known that the homogenous dispersion and distribution of particles introduced to the elastomer matrix affects the elastomerfiller interaction and thus the useful parameters of vulcanizates. Several authors have used silanes for enhancing the interfacial interactions and thus the compatibility between elastomers and fillers [24][25][26]. The application of ionic liquids is also known to positively affect the dispersion of filler and curatives and thus the properties of vulcanizates [27][28][29].…”
Section: Introductionmentioning
confidence: 99%